Community-driven tree planting in Northern Namibia : Determinants and challenges - Pratiwi, Ayu; Huttunen, Sanna; Ndeinoma, Albertina; Lisao, Kamuhelo; Ndeunyema, Elizabeth; Amuthenu, Ndapandula; Haufiku, Anna; Myllynpää, Ville (France, 2026)
Climate change and environmental degradation are among the most pressing global issues, making tree planting initiatives essential for combating climate change, halting biodiversity loss, and restoring degraded landscapes. However, many tree planting programs face challenges such as planting non-native, potentially invasive species, and disregarding community preferences. Therefore, for successful tree planting programs, community input should be strongly considered, such as considering the multi-purpose trees’ functionality and primary socioeconomic factors affecting tree planting. This paper examines the community preferences for native species, as well as household-level determinants and challenges affecting tree planting programs, utilizing a unique dataset from northern Namibia. Using a multilevel logistic regression model, we found that low-income households with larger landholdings are more likely to participate in tree planting initiatives. In contrast, households with members engaged in non-farm employment are less inclined to start or continue planting even when provided with seedlings, as they may prefer more stable and low-risk income streams. We recommend that future tree planting programs align with household preferences for tree purposes and provide sufficient economic incentives to ensure the sustainable maintenance of planted species.
The Frontier in Sustainable Agromaritime and Environmental Development Conference (FiSAED 2024), Bogor, West Java, Indonesia, December 19-20, 2024